“O Latim da Terra”: Políticas, intercâmbios e usos da Língua Geral no Grão-Pará e Maranhão (1750-1777) - SILVEIRA, Arlindyane Santos da (2023)
The work presented to the reader aims to mainly analyze the local and imperial dynamics embedded in the Portuguese State's power and control project that sought the suppression of the General Language and the consequent officialization of the Portuguese Language in the Luso-Amazonian society, especially in the region of Grão-Pará and Maranhão between the years 1750 and 1777. This project of dominance over language use was inserted, above all, in the broader process of the constitution of a Luso-Amazonian society in the region and, in this sense, this study conducts a mapping of the linguistic policies, the subjects and social uses of the General Language, as well as the construction of discourses and strategies undertaken by the Portuguese government and other historical agents of the colonial scenario. What is here supposed to be a project of dominance over linguistic knowledge in the period covered in this work, is a process of social normalization allied to practices that homogenized and hybridized the existing linguistic diversity in American lands in the 17th century, while at the same time redrawing local dynamics of adjustments and negotiations that were built parallel to the progressive establishment of the Portuguese Language in Amazonia from the mid-18th century. In this scenario, some elements stand out and shape the main elements of this work: the action of missionaries and their own linguistic policies, especially those of the Society of Jesus, the Pombaline policies that impacted the linguistic issues more systematically from the establishment of the Indian Directorate, and, mainly, the exchanges and re-significations that various subjects, in Maranhão and Pará from the mid-18th century, produced to resist, modify, and locally adjust to their own interests the restriction of the use of the General Language and the determination of the exclusivity of the Portuguese Language, in the context of the guidelines of a supposedly civilizing-oriented linguistic control project.